Effect of tube location on the temperature of plate lithium-ion battery applicable in the aerospace industry in the presence of two-phase nanofluid flow inside a channel placed in phase change material. (May 2023) - Chen, Haiji; Zhou, Wanlin; Yuan, Yanjie; Heidarshenas, Behzad
Abstract: This article presents three-dimensional simulations of the cooling system of a plate lithium-ion battery (BTY) using the finite element method (FEM). Since weight is of particular importance in the aerospace industry, this type of batteries can be used. The cooling system consists of two enclosures containing phase change material (PCM) on both sides of the BTY cell and alumina/water nanofluid flows in a tube in the middle of the PCM. This simulation is performed using the two-phase model. By changing the nanofluid velocity (VNF) from 10 to 30 mm/s and changing the location of the tube in the PCM enclosure, the temperature contours of the BTY, PCM, and tube, as well as the contours of PCM melting and volume fraction (VFN) of molten PCM are provided. According to the findings, increasing the VNF from 10 to 30 mm/s decreases the average temperature of the BTY (TBT) by 14.8% and the VFN of molten PCM by 18.9% in 1200 s. Also, when the tube distance is 8 mm, the TBT is minimal and the amount of solid PCM is maximal. When the tube distance is 11 mm, the TBT is maximal and the VFN of solid PCM is minimal.